Integrating Technology into Physical Education Curricula: A Framework for Enhancing Student Engagement - DUMBUYA, Emmanuel (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
This paper explores the integration of technology into Physical Education (PE) curricula, focusing on how digital tools and mobile applications can enhance student engagement and improve learning outcomes. A framework is proposed for incorporating these technologies effectively into both in-class activities and out-of-class learning experiences. Through a mixed-methods research approach, this study investigates the potential of digital tools in transforming PE education, the barriers to successful integration, and the pedagogical benefits of using such technologies. The findings offer practical recommendations for educators and policymakers aiming to modernize physical education programs. Article history: Received 2025 February 01; Revised 2025 March 19; Accepted 2025 March 20. Available online 2025.03.30; Available print 2025.05.30